2022
DOI: 10.1111/1440-1630.12791
|View full text |Cite
|
Sign up to set email alerts
|

Levelling the playing field: Exploring inequalities and exclusions with a community‐based football league for people with experience of mental distress

Abstract: Introduction Sport workforce strategy in the United Kingdom (UK) has identified the occupational therapy profession as being ideally positioned to contribute to public health agendas relating to tackling physical inactivity amongst marginalised populations, such as disabled people and people with experience of mental distress. However, a robust understanding of the enablers, restrictions, and exclusions such groups encounter when seeking to participate in sport and physical activity is currently lacking. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Fourteen of the included articles pointed out that participatory approaches enable individuals living with mental illness to express what really matters to them to create relevant and meaningful knowledge (see Table 2 ). Three of the included studies ( Pettican et al, 2021 ; Pettican et al, 2022 ; Tsatsi & Plastow, 2021 ) suggested that involving persons with mental illness in conducting research can assist both mental health consumers and mental health professionals such as occupational therapists to identify important ideas and the desired direction for change. In two studies, authors ( Dixon et al, 2022 ; Rempfer & Knott, 2002 ) noted that including the voice of mental health consumers helps occupational therapists access the knowledge not represented in the scientific literature.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen of the included articles pointed out that participatory approaches enable individuals living with mental illness to express what really matters to them to create relevant and meaningful knowledge (see Table 2 ). Three of the included studies ( Pettican et al, 2021 ; Pettican et al, 2022 ; Tsatsi & Plastow, 2021 ) suggested that involving persons with mental illness in conducting research can assist both mental health consumers and mental health professionals such as occupational therapists to identify important ideas and the desired direction for change. In two studies, authors ( Dixon et al, 2022 ; Rempfer & Knott, 2002 ) noted that including the voice of mental health consumers helps occupational therapists access the knowledge not represented in the scientific literature.…”
Section: Methodsmentioning
confidence: 99%
“…Across both sport and physical activity and occupational therapy PAR research, creative methods have been used to subvert conventional approaches to knowledge production. For example, podcasting (Smith, Danford et al 2021a), photovoice (Birken and Bryant 2019;Hayhurst and Centeno 2019;McSweeney et al 2022), WhatsApp© conversations (Dania and Griffin 2021), World Cafés (Pettican, Speed et al 2021) and goalong interviews (Pettican et al 2022). Within the occupational therapy literature, the principles and practices of PAR have also been related to professional skills, philosophies and knowledge translation (Wimpenny 2013;Kramer-Roy 2015;Bennett et al 2016).…”
Section: Co-production and Parmentioning
confidence: 99%
“…Even if this exclusion is unplanned or inadvertent, when policy is not informed by their experiences, their marginalised status is reinforced (Redwood, Gale, and Greenfield et al 2012;Beresford 2013b). The findings from the PMA research project have been an important counter in this regard, highlighting the need for broader social change outside of specialist provision (Pettican et al 2022). These findings are now informing policy and practice within Sport for Confidence CIC, where the first author is working with participants, coaches and national governing bodies of sport to enable participation in physical activity for marginalised populations (Pettican and Barrett 2017;Pettican, Bullen et al 2021).…”
Section: Aligning Par and Co-productionmentioning
confidence: 99%